The Effect Of Financial Development On The Insurance Activity In Algeria - Benziane, Dalila; Oukaci, Kamal (University of Eloued جامعة الوادي, 2019)
Our study describes the co-integration relation between the financial and the insurance sectors. Indeed, it consists in repeating and verifying the empirical results obtained in previous studies concerning the existing link between the insurance sector and the financial sector. The studies that looked at the relationship between financial development or banking development and growth in the insurance sector are very minimal, but all these studies find a positive correlation of these financial variables with the insurance market mainly in Outreville (1990,1996), Carson et al., (2014) and Ward and Zurbruegg (2002). Using the ARDL model to estimate the relationship between the penetration rate and financial variables in Algeria between 1974 and 2015, it is shown that there is indeed a short and long-term relationship between certain variables that measures the level of financial development. These are the quasi-currency rate and the level of credit to the private sector. As for the relationship of insurance to economic growth, we have found an absence of a relationship that ranges from economic growth to penetration rates
مجلة رؤى المجلد التاسع العدد الأول
Keywords: Insurance; Financial development; Economic growth; ARDL; Algeria. (JEL) Classification : G22, G20